A methodology for variable amplitude fatigue analysis of HFMI treated welds based on fracture mechanics and small-scale experiments. (September 2016) - Ghahremani, Kasra; Walbridge, Scott; Topper, Tim
Highlights: Strain-based fracture mechanics and an effective strain-life models are incorporated. A crack closure model and the residual stress state are included in the methodology. The methodology does not require a fine grid, non-linear finite element analysis. Crack closure and crack growth parameters for 350W steel are determined. The strain-based fracture mechanics model is evaluated using fatigue tests results. Abstract: A methodology is developed using strain-based fracture mechanics (SBFM) and an effective strain-life (ESL) model for the fatigue analysis of as-received and high frequency mechanical impact (HFMI) treated structural steel welds. The methodology includes a crack closure model and accounts for the residual stress state at the weld toe. Several required input parameters for mild structural (CSA 350W) steel were obtained using relatively simple and inexpensive small-scale fatigue tests of smooth specimens, conventional monotonic and cyclic materials tests, laboratory measurements, and residual stress measurements. The ESL modelling component of the methodology is validated using direct crack growth measurements. The SBFM model is evaluated using the results of fatigue tests on weld specimens and is found to be capable of accurately or conservatively predicting the fatigue performance of the as-received and impact treated welds under one constant and two variable amplitude loading histories.